(untitled) (Jurnal Anestesi Perioperatif, 2020)
Iron deficiency remains the most prevalent micronutrient deficiency worldwide. Iron deficiency in TB patients, causes a poor outcome, reccurency, and treatment failure. Iron supplements on TB patients with iron deficiency will activate macrophage-derived monocytes (MDM) and interferon-gamma (IFN-Î³), with a positive feedback mechanism pushing interleukin-12 (IL-12). This study is a single-blind randomized control trial comparing the effectivity of preoperative iron supplementation in IL-12 level between two different groups in Dr. Hasan Sadikin General Hospital Bandung, conducted from November 2018 until March 2019. Respondents are those having Spondylitis TB, with sTfR > 21,7 pg/mL and IL-12 <41 pg/mL, intensive phase antituberculosis drugs category 1. The experimental group, comprised 17 respondents, was treated with 2RHZE and 357mg iron (III) hidroxy polymaltosa. The control group was treated with 2RHZE. The sTfR and IL-12 levels were performed before and after treatment. The increase of IL-12 in the experimental group was +364,53% higher than in the control group (p<0.05). The decrease of sTfR in the experimental group was -60,68% higher than in the control group (p<0.05). The result of the Pearson correlation test was a coefficient correlation of - 0,73, this showed that a decrease in the sTfR level correlated with an increase in the Il-12 level. Iron supplement in Spondylitis TB with iron deficiency in the experimental group increases the IL-12 level. Preoperative iron supplementation on spondylitis TB with iron deficiency, increases the immune system with higher levels of IL-12. Perbedaan Kadar IL-12 pada Terapi Pre-Operatif Spondilitis TB dengan Defisiensi Zat Besi yang diberikan Suplementasi Zat Besi Defisiensi Fe merupakan defisiensi mikronutrien paling sering di seluruh dunia, jika terjadi pada penderita TB akan meningkatkan risiko prognosa buruk, rekurensi, MDR, dan gagal terapi. Suplementasi besi pada tuberkulosa dengan defisiensi besi akan meningkatkan sistem imun dengan mengaktivasi macrophage derived monocyt, dan interferon-gamma, dengan mekanisme umpan balik positif memacu interleukin-12. Single blind randomized control trial untuk membandingkan efektivitas Fe terhadap kenaikan IL-12 pada terapi preoperatif spondilitis TB di RSHS periode Nopember 2018- Maret 2019. Metode sampling;consecutive sampling. Subjek sebanyak 34 orang; Penderita spondilitis TB, sTfR >21,7 pg/ml dan IL-12< 41 pg/mL. fase intensif OAT kategori 1sesuai dengan standar WHO. Kelompok eksperimen, 17responden diterapi 2 RHZE + tablet iron (III) hidroksi polimaltosa357 mg selama 2 bulan. Kelompok kontrol 17 responden diterapi 2RHZE. Peningkatan IL-12 pada kelompok eksperimen sebesar +364,53% lebih besar dari kelompok kontrol (p<0,05) dan; Penurunan kadar sTfR pada kelompok eksperimen sebesar –60,68% (p<0,05) lebih besar dari kontrol. Uji korelasi sTfR dan IL-12 dengan Pearson ; korelasi -0,763, menunjukkan korelasi kuat antara penurunan sTfR dan kenaikan nilai IL-12. Suplementasi Fe pada terapi preoperatif spondilitis TB dengan defisiensi Fe meningkatkan respon imun yang ditandai dengan meningkatnya IL-12.